Influence of corn silage supplementation before alfalfa grazing on ruminal environment in relation to the occurrence of frothy bloat in cattle - Bretschneider, Gustavo; Peralta, M.; Santini, Francisco Jose; Fay, Jose Patricio; Faverin, Claudia (Elsevier, 2023)
Changes in the ruminal environment of cattle supplemented with corn silage (CS) before alfalfa grazing, in relation to the occurrence of frothy bloat, were evaluated. Six ruminally fistulated heifers were used in a crossover design experiment for in situ determinations and as a source of rumen fluid for in vitro measurements. Alfalfa pasture was grazed at the vegetative stage in a rotational grazing system. Treatments were—C: no supplement; CS: 0.5 kg of CS dry matter/100 kg body weight. CS supplementation reduced (P<0.05) the frequency and severity of frothy bloat. From the sixth hour until the end of the incubation at 12 h, in vitro microbial gas production using alfalfa leaflets as substrate was lower in rumen fluids from CS supplemented heifers. Bacterial mass in the liquid phase of ruminal contents, and in situ microbial colonization of particles entering the rumen did not differ. Only at 4 h post-grazing was proteolysis reduced (P<0.05) for both treatments. The anti-bloat mechanisms of CS were not completely identified, however we confirmed that CS supplementation before alfalfa grazing is a reliable management practice to reduce frothy bloat.